2012
DOI: 10.1016/j.jinsphys.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of long-chain hydrocarbons in the aggregation behaviour of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae)

Abstract: a b s t r a c tThe multicoloured Asian ladybirds, Harmonia axyridis (Pallas), form large aggregations inside dwellings to survive cold winters, causing annoyance to householders due to their abundance, allergenic properties and problems consequent on reflex bleeding. Flight to overwintering sites and macrosite choice of this species is well documented. H. axyridis shows a hypsotactic behaviour and a clear preference for contrasting visual elements. However, how the microsite is selected remains undocumented, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Overwintering individuals are also more likely to follow this chemical mark than individuals collected in spring or summer. The overwintering surface is also chemically marked with a similar chemical blend, comprising the same molecules but in different ratios (Durieux et al, 2012). This suggests there are two different blends of long-chain hydrocarbons, the first leading conspecifics toward aggregation sites and the second ensuring the cohesion of the aggregate.…”
Section: Aggregationmentioning
confidence: 95%
See 2 more Smart Citations
“…Overwintering individuals are also more likely to follow this chemical mark than individuals collected in spring or summer. The overwintering surface is also chemically marked with a similar chemical blend, comprising the same molecules but in different ratios (Durieux et al, 2012). This suggests there are two different blends of long-chain hydrocarbons, the first leading conspecifics toward aggregation sites and the second ensuring the cohesion of the aggregate.…”
Section: Aggregationmentioning
confidence: 95%
“…During aggregation, adult H. axyridis show mutual interactions, and should therefore be considered as social aggregators. In addition to the physical contacts between congeners (Durieux et al, 2014a), laboratory assays have shown that chemical markings are involved in this aggregation behavior (Durieux et al, 2012). Non-volatile long-chain hydrocarbons are passively deposited by walking males and females on the surfaces surrounding the aggregation site (Kosaki and Yamaoka, 1996;Durieux et al, 2012).…”
Section: Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative attractiveness of different 411 surface colours has been studied; white is the most attractive colour followed by yellow and black 412 then green then red and finally natural wood (Wang et al 2011). Volatile aggregation pheromones 413 are not involved in this orientation (Nalepa et al 2000) but it is apparent that contact 414 chemoreception is important in the establishment of large aggregations (Durieux et al 2012). 415…”
mentioning
confidence: 99%
“…It is considered to be bivoltine but up to five generations per year have been observed (Bazzocchi et al, 2004;Nedved and Honek, 2012). In winter months, the species aggregates in concealed and sheltered locations that provide a protective microclimate (Berkvens et al, 2010;Wang et al, 2011;Durieux et al, 2012;Raak-van den Berg et al, 2012). It might be advantageous for a female to be fertilized before leaving these overwintering aggregation sites, as this would allow females to found populations even without males .…”
Section: Introductionmentioning
confidence: 99%